CORPORATE ENTREPRENEURSHIP, STRATEGIC APPROACHES FOR GENERICS AND FIRM SUCCESS IN SMALL AND MEDIUM ENTERPRISES - Sitikantha Mishra, Bibhuti B Pradhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Organizations have more and more adopted proactive management strategies to withstand vigorous competition in today's intensely dynamic market environment. Companies operate in a context that can influence the pursuit of strategies positively and negatively. Strategies offer a roadmap for the future of an organization as action paths to accomplish objectives; however, they do not inherently imply a competitive advantage for companies. Alternatively, the competitive advantage is a product of efficient execution of strategic strategies. The literature on the strategy is full of studies based on factors such as entrepreneurship and distinction at the strategic and cultural firm level. Research suggests these factors are significant long-term determinants of superior firm efficiency. Nevertheless, most of the works in this field have concentrated on big, multinational corporations. The impact of entrepreneurship and distinction on the financial results of small and medium-sized enterprises (SMEs) are still little understood. In the present research, using a sample of 70 SMEs from the Turkish Machinery and Equipment Manufacturing Industry, It was analysed that the impact of these three crucial factors on firm results the findings indicate that SME output is positively affected by competitiveness and differentiation in companies. The theoretical and organizational consequences of the results of the analysis are discussed.